Determinantes de la inversión pública de los gobiernos distritales del departamento de Ayacucho, 2008-2023 - Palomino Moisés, Marco Antonio (2024)
This study analyzes the determinants of public investment by the district governments of Ayacucho in the period 2008-2023, using a fixed-effects balanced microeconomic data panel model with 1,600 observations. The financing items and the political cycle were considered as regressor variables. The financing items evaluated, according to the Ministry of Economy and Finance (MEF), include: i) Ordinary Resources, ii) Municipal Compensation Fund, iii) Canon (redistributed tax revenue from extractive industries) and Royalties, Customs Revenue and Participations, iv) Donations and Transfers, v) Resources from Official Credit Operations, vi) Municipal Taxes, and vii) Directly Collected Resources. The political cycle was defined by the first three years of local management. The results show that the following items: i) Ordinary Resources, ii) Municipal Compensation Fund, iii) Canon and Royalties, iv) Donations and Transfers, v) Resources from Official Credit Operations, and vi) Municipal Taxes are significant and positive for public investment, while Directly Collected Resources are not. The analysis of the political cycle shows that the first, second and third year of municipal management have a significant and negative effect on public investment. In conclusion, ordinary resources, donations and transfers, the municipal compensation fund and municipal taxes are positive determinants of investment. Canon and Royalties are positive when they exceed S/ 2,505.977 (percentile 75). However, directly collected resources are not determinants and the political cycle of the first three years has a negative impact on investment.